56 INSULIN DECREASES LUNG INFLAMMATION AND ACUTE LUNG INJURY IN RATS. (1st January 2006) - Repine, J. D.; Elkins, N. D.; Fini, M.; Wright, R. M.; Repine, J. E.
Abstract : Intensive insulin therapy not only normalizes the elevated blood glucose levels that develop in nondiabetics and diabetics who are battling critical illnesses but also, and remarkably, increases the survival of these individuals (N Engl J Med 2001;345:1359-67 and J Clin Invest 2004;114:1187-95). To begin to determine the presently unknown mechanism for this lifesaving effect, we hypothesized that insulin therapy decreases lung inflammation and acute lung injury seriously ill patients. We chose to initially test this premise using a standard rat model in which lung inflammation and acute lung injury develop following insufflation of cytokines (interleukin-1 and/or interferon-γ) that are increased in lungs of patients with acute lung injury. We found that insulin therapy decreases lung neutrophil recruitment (lung lavage neutrophil counts) and acute lung injury (lung lavage LDH concentrations) in lungs of cytokine insufflated rats. In addition, insulin therapy also decreased xanthine oxidoreductase (XOR) activity in mononuclear phagocytes recovered by lavage from lungs of cytokine insufflated rats. The latter observation is relevant because our prior studies suggest that mononuclear phagocyte XOR activity may contribute to neutrophil increases in lungs of rats insufflated with cytokines (Am J Respir Cell Mol Biol 2004;30:479-90). In parallel, we found that inducing hyperglycemia (without administering insulin) increased the number of neutrophils recoverable from lungs of rats insufflated with cytokines. These preliminary findings suggest that one possible effect of intensive insulin therapy is to reduce lung inflammation and acute lung injury. This mechanism might contribute to the reduced mortality of critically ill patients who receive intensive insulin therapy.